Effect of Aggregates with Different Physical Properties on Concrete Strength for Different Water to Cement Ratio and Different Cement Content - Tugrul, Esra (My University, 2020)
Aggregates have a large volume in concrete, therefore they directly affect the properties of concrete.Aggregate, which is expected to give desirable strength in concrete, should be examined especially interms of its physical properties and grain size. In this respect, aggregate to be used in concrete mustnot be easily broken, non-abrasion quickly, and must be strong and hard structure. While low strengthis obtained in concrete produced with porous lightweight aggregates, high strength is observed inconcrete produced with high-density aggregates. In addition, aggregates have an effect on concreteproperties such as concrete workability and permeability. One of the aggregates commonly used inconcrete production is limestone aggregate. In this study, the effects of limestone aggregates withdifferent properties on compressive strength and splitting tensile strength were investigatedexperimentally. In this context, cubic specimens of 150×150×150 mm dimensions were prepared fordifferent water/cement ratios, different cement contents, and different aggregate properties. Withthese specimens, after the cure period of 28 days, the relevant strength tests were performed. Thestrength values of these concrete specimens were compared and the results were discussed. As a result;it has been determined that the concrete strengths obtained by considering the relevant standards arecompatible with the literature. Thus, in this study, it has been determined that aggregates tested foruse in concrete have positive effects on concrete strength.
Keywords: Malzeme Bilimleri; Tekstil; İnşaat Mühendisliği; Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Kâğıt ve Ahşap; Malzeme Bilimleri; Kaplamalar ve Filmler; Malzeme Bilimleri; Biyomalzemeler; Malzeme Bilimleri; Seramik; Malzeme Bilimleri; Kompozitler